A figura da bruxa no contexto das visitações no Brasil setecentista: um contributo do imaginário de Gilbert Durand - Resende, Elle Beethoven dos Santos (2019)
The present work is the development of research on how the clerical construction of the mythical figure of the witch occurred. For this study, were analyzed sources of inquisitorial historiography, aiming to understand the various contexts in which the female gender is absorbed by the mythical symbolism, deriving from the current clerical empowerment that provided these women moments of misogynist confrontation, through disrespect and criminalization for centuries. Starting in quest of the understanding of when this mythology was broadened and stated, specifically, from the period in which the Portuguese Inquisition (1536-1821) acted, when intolerance was established as a consequence of the cosmogonic experiences of its daily life. Thus, the possible mythical birthplaces of the witch were privileged in this study; understanding its symbolic consolidation in the collective mentality and, finally, promoting a rereading of the relationship between clerical power and the pedagogy of fear. To this end, it will be ascertained distinct opinions that are part of the founding theoretical framework of this dissertation, which will provide insightful understanding of the symbolic universe of the witch and its mythical construction becoming visible in post-apostolic angelic voices and entered the imagery of popular credulity as steadfast truths. As a triad, Jean Delumeau (1989), in his work, La peur en Occident (XIVe – XVIIIe siècles): une cité assiégée, will be approached first, which takes as its object of study the multiform of fear present in the individual and the collective. We will then use Gilbert Durand (1995), L’imag in ation symbolique and La Foi du Cordonnier, from the conception of how images are produced, transmitted and how they are received. Finally, in the lens of Michel Foucault (2018) in his work, Surveiller et punir, one perceives the discipline and imprisonment of the human being in authoritative regimes.